Georgie, all along - Clayborn, Kate (Kensington Publishing Corp., 2023)
"Longtime personal assistant Georgie Mulcahy has made a career out of putting others before herself. When an unexpected upheaval sends her away from her hectic job in L.A. and back to her hometown, Georgie must confront an uncomfortable truth...But then Georgie comes across a forgotten artifact--a 'friendfic' diary she wrote as a teenager...a guidebook for getting started on a new path. Georgie's plans hit a snag when she comes face to face with an unexpected roommate...But this quiet, grouchy man is more than just his reputation, and he offers to help Georgie with her quest. As the two make their way through her wishlist, Georgie begins to realize that what she truly wants might not be in the pages of her diary after all"--